Host Immune Responses to Clostridioides difficile: Toxins and Beyond - Nibbering, Britt; Gerding, Dale N.; Kuijper, Ed J.; Zwittink, Romy D.; Smits, Wiep Klaas (Frontiers in Microbiology, 2021)
Clostridioides difficile is often resistant to the actions of antibiotics to treat other bacterial infections and the C. difficile infection (CDI) that can result is among the leading causes of nosocomial infectious diarrhoea worldwide. The primary virulence mechanism contributing to CDI is the production of toxins. Treatment failures and recurrence of CDI have urged the medical community to search for novel treatment options. Strains that do not produce toxins, so called non-toxigenic C. difficile, have been known to colonise the colon and protect the host against CDI. In this review, a comprehensive description and comparison of the immune responses to toxigenic C. difficile and non-toxigenic adherence, and colonisation factors, here called non-toxin proteins, is provided. This revealed a number of similarities between the host immune responses to toxigenic C. difficile and non-toxin proteins, such as the influx of granulocytes and the type of T-cell response. Differences may reflect genuine variation between the responses to toxigenic or non-toxigenic C. difficile or gaps in the current knowledge with respect to the immune response towards non-toxigenic C. difficile. Toxin-based and non-toxin-based immunisation studies have been evaluated to further explore the role of B cells and reveal that plasma cells are important in protection against CDI. Since the success of toxin-based interventions in humans to date is limited, it is vital that future research will focus on the immune responses to non-toxin proteins and in particular non-toxigenic strains.